Proposed occupational health and safety policy for the University of the Philippines Diliman Library System - Gutierrez, Giancarla Therese L.; Encanto, Joenabie A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
Libraries are no different from other places of employment. Health hazards are also present in the libraries. Having no policy to guide the employers and employees in preventing any occupational health accidents or injuries, health hazards continue to persist and cause discomfort among the library staff.
The main objective of this study is to formulate the proposed occupational health and safety policy (OHSP) for the University of the Philippines Diliman Library System (UPDLS). Along with this study, this study seeks to (1) determine the specific workplace hazards that the policy need to focus on; (2) know what are the managers' responsibilities, that will guide them in providing a healthy and safe workplace for their employees; (3) find out what are the responsibilities of employees that will ensure their health and safety.
The computed sample size for this study is 123 respondents from the population of 180 employees of the UPDLS. Only 79 (64%) respondents were gathered. Based on the responses it was found out that majority of the respondents agreed on having an OHSP for their library.
The respondents have strongly agreed that the Chemicals used in the Microfilm Laboratory, 51 (64.56%); Shelves, 41 (51.90%); Ventilation, 40 (50.63%); Lighting/Illumination, 39 (49.37%); and Space Requirement, 39 (49.37%) are the hazards that should be given priority in their inclusion in the OHSP.
Among the 12 responsibilities of managers enumerated in the questionnaire, five are included in the proposed OHSP; (1) identifying the health hazards present in the library; (2) taking all practical steps to minimize the likelihood that the hazard will cause harm to the employees; (3) ensuring that employees are given proper medical attention; (4) helping employees seek medical attention further if discomfort or symptom continues to persist; (5) monitoring, with informed consent of employees, their health in relation to exposure to the hazard.
From the 11 responsibilities of employees enumerated in the questionnaire, five are included in the proposed OHSP; (1) ensuring that no action or inaction will cause harm to himself or other person; (2) attending programs, trainings, symposiums, about occupational health and safety provided by the institution he/she is employed in; (3) reporting any problem with the equipment, work flow, or personal health to the manager; (4) taking all practical steps to ensure his safety while at work; (5) reporting suspected occupational health and safety hazard that causes discomfort.
To further improve the proposed OHSP, the researcher recommends that more academic libraries should be included in the survey and have the proposed OHSP, evaluated by the Occupational Health and Safety Center of the National Institute of Health.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman. -- Library; Library employees -- Medical care